2020
DOI: 10.4103/jhrs.jhrs_211_20
|View full text |Cite
|
Sign up to set email alerts
|

Resuming Assisted Reproduction Services during COVID-19 Pandemic: An Initial Indian Experience

Abstract: Background: The pandemic of COVID-19 has affected many countries and medical services including assisted reproductive treatment (ART) have been hampered. Aim: The study was conducted to assess the preparedness of ART clinics and staff to resume services; patients' reasons to initiate treatment; and key performance indicators (KPIs) of ART laboratories during the pandemic. Setting and Design: This was a semidescriptive, prospective study in tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The COVID‐19 pandemic affected ART treatment cycles worldwide by causing the cessation of new treatments, delays and postponements of treatment, and changes or interruptions of the stimulation protocols for couples undergoing ART. 22 , 23 , 24 , 25 , 26 , 27 In Japan, literature on the effects of the COVID‐19 pandemic on ART facilities, services, outcomes, and patients is limited and detailed analyses have yet to be conducted. However, the COVID‐19 pandemic was considered to have little effect on decreasing the total number of ART cycles implemented during 2020 compared with other European countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 pandemic affected ART treatment cycles worldwide by causing the cessation of new treatments, delays and postponements of treatment, and changes or interruptions of the stimulation protocols for couples undergoing ART. 22 , 23 , 24 , 25 , 26 , 27 In Japan, literature on the effects of the COVID‐19 pandemic on ART facilities, services, outcomes, and patients is limited and detailed analyses have yet to be conducted. However, the COVID‐19 pandemic was considered to have little effect on decreasing the total number of ART cycles implemented during 2020 compared with other European countries.…”
Section: Discussionmentioning
confidence: 99%
“…28 Similar concerns and desires were voiced by patients in other countries who also experienced cancellations or delays in ART cycles. 25 , 26 After the first statement issued by the JSRM to patients, a web questionnaire survey conducted in August 2020 by a non‐profit organization in support of patients with infertility issues revealed that many patients were concerned about COVID‐19. Many wanted to continue ART treatments, especially those aged >40 years, and a large number of patients asserted that infertility treatments are not “non‐essential and non‐urgent” matters, which posed an important ethical dilemma at the time.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian study by Jirge et al provides practical insights for the resumption of ART services in India and found satisfactory Key Performance Indicators (KPIs) for cycles conducted in the COVID era; however, clinical indicators were not compared. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic also negatively influenced IVF and ART. A study showed that 62% of women undergoing infertility treatment deferred their procedures due to lack of safe transportation, 20% of cases delayed treatment due to financial reasons, and 9% of couples declined due to fear of the pandemic [ 9 ].…”
Section: Assisted Reproductive Technology Challengesmentioning
confidence: 99%